Effect of NaBr, KCl, KBr, and MgCl2 on viscosities of aqueous glycine and L-alanine solutions at 298.15 K - Badarayani, Rohini; Satpute, D. B.; Kumar, Anil (Journal of Chemical and Engineering Data, 2005)
Viscosities, η, of glycine and L-alanine are measured in aqueous solutions of NaBr, KCl, KBr, and MgCl2 up to high concentrations at 298.15 K. This study suggests that 1:1 electrolytes enhance the structure making ability of the amino acids whereas MgCl2 does not. The viscosities of the above solutions are correlated using a simple model with two interaction parameters.